PENGEMBANGAN MODEL PERSAMAAN HIDROLIK BENTUK TERTUTUP UNTUK PENENTUAN TEKANAN FLUIDA PENGEBORAN PADA KASUS SUMUR PANAS BUMI DI INDONESIA - Eko Abdurrahman, Nur
The Guo-Ghalambor (2003) equation is a closed form hydraulics equation used to determine the pressure value of multiphase drilling fluid in hydrocarbon well drilling. This study is developed to determine the compatibility of the equation in a geothermal well drilling operation. A simple Excel program is developed out of this equation to ease the use for practice, and this program is used to determine the compatibility of the pressure value with the fluid hydrostatic pressure data. This resulted in the program with 3.67% error margin against literature data. When validated with IMN well data, the obtained value has error margin of 9% to 32% against drilling fluid hydrostatic pressure data. In getting the accurate pressure value from the program, a sensitivity analysis was done for one of the assumed parameters, which is choke pressure. The result of the sensitivity is a varied between 59.2 psia to 147.6 psia, compared to the assumed value of 50 psia.